2021
DOI: 10.1186/s12864-021-07593-3
|View full text |Cite
|
Sign up to set email alerts
|

Dense time-course gene expression profiling of the Drosophila melanogaster innate immune response

Abstract: Background Immune responses need to be initiated rapidly, and maintained as needed, to prevent establishment and growth of infections. At the same time, resources need to be balanced with other physiological processes. On the level of transcription, studies have shown that this balancing act is reflected in tight control of the initiation kinetics and shutdown dynamics of specific immune genes. Results To investigate genome-wide expression dynamics… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 107 publications
2
38
0
Order By: Relevance
“…coli ( Fig 1C ). This result is consistent with a recent time course study that found Toll-regulated genes (including BaraA ) were rapidly induced after injection stimulating the Imd pathway, but this principally Imd-based induction resolves to nearly basal levels within 48 hours [ 22 ] (and see S1B and S1C Fig ). Additionally, larvae pricked with M .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…coli ( Fig 1C ). This result is consistent with a recent time course study that found Toll-regulated genes (including BaraA ) were rapidly induced after injection stimulating the Imd pathway, but this principally Imd-based induction resolves to nearly basal levels within 48 hours [ 22 ] (and see S1B and S1C Fig ). Additionally, larvae pricked with M .…”
Section: Resultssupporting
confidence: 92%
“…Monitoring GFP in BaraA-Gal4>UAS-mCD8-GFP flies (referred to as BaraA>mGFP) confirms that the BaraA reporter is highly induced in the fat body after infection by M. luteus, but less so by E. coli (Fig 1C). This result is consistent with a recent time course study that found Toll-regulated genes (including BaraA) were rapidly induced after injection stimulating the Imd pathway, but this principally Imd-based induction resolves to nearly basal levels within 48 hours [22] (and see S1B and S1C Fig) There was also sporadic GFP signal in other tissues that included the larval hindgut, the dorsal abdomen of developing pupae, and the seminal vesicle of males. [11]).…”
Section: Baraa Is Regulated By the Toll Pathwaysupporting
confidence: 92%
See 1 more Smart Citation
“…Activity on the first day of infection was predictive of lifespan, with more active flies exhibiting increased lifespan (Figure 1E). In addition, there was a positive correlation between total activity and survival (Figure 1 – figure supplement 1F); we used day one activity as a predictor because previous work has found immune activity to be strongest at this time (De Gregorio et al, 2002a; Lemaitre et al, 1997; Schlamp et al, 2021) and thus would be an appropriate metric in looking at infections of shorter duration. Furthermore, day 1 activity levels were positively correlated with total activity levels (Figure 1 – figure supplement 1G), giving us confidence that activity on day 1 is representative of total activity levels in assessing infections of longer duration.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of gene expression at regular intervals throughout an infection has demonstrated that the host immune response is a dynamic process which needs to be initiated and sustained to fight an infection. 48,49 At 24 hours post-infection, the timepoint at which RNA was collected for gene expression analysis, animals infected with P. aeruginosa were much closer to dying than animals infected with P. rettgeri (N2 P. aeruginosa LT50 = 3.8 ± 0.3 days, CB4856 P. aeruginosa LT50 = 3.5 ± 0.3 days; N2 P. rettgeri LT50 = 7.8 ± 0.7 days, CB4856 P. rettgeri LT50 = 7.2 ± 0.6 days). Perhaps animals exposed to P. aeruginosa or P. rettgeri are at two different stages in combatting their respective infections and the overlap in gene expression between N2 and CB4856 animals grows larger as animals progress from earlier to later stages of infection.…”
Section: Individual Pathogens Induce Different Responses In C Elegans Isolatesmentioning
confidence: 99%